Brug af input-output-metoder og højfrekvente indikatorer ved vurdering af BNP-udviklingen i 2020 - Adrian Michael Bay Schmith; Rasmus Rold Sørensen; Morten Werner (Danmarks Nationalbank, 2020)
– The memo gives a technical summary of a system developed and used in Danmarks Nationalbank's assessment of the economic impact of the covid-19 crisis. The system combines input-output tables from the national accounts, the input-output model and Danmarks Nationalbank's high-frequency indicators. This allows for a high degree of details with regard to industries and final demands combined with high frequencies indicators for subgroups of private consumption possibly of daily frequencies.
Keywords: 330; Input-Output-Analyse; Wirtschaftsindikator; Nationaleinkommen; Coronavirus; Wirkungsanalyse; Dänemark